Risk factors for deep venous thrombosis following total hip arthroplasty: a meta-analysis - Tao Wang; Qi Zhang; Zhiyong Hou (Thrombosis Journal)
Abstract Objective We aim to investigate the predictors of deep venous thrombosis (DVT) following total hip arthroplasty (THA) by meta-analysis. Methods We collected potential indicators of DVT from related literature in the English databases of PubMed, Embase, and the Cochrane Library. We used RevMan 5.3 and STATA 12.0 to analyze potential indicators of DVT after THA. Results Finally, there were 6 English articles included in our study, and the rate of DVT after THA was 18.9% (270 of 1428 patients). Our findings indicated that advanced age [p<0.00001, OR = 4.51, 95% CI (2.91, 6.10)], female patients [p = 0.008, OR = 0.65, 95% CI (0.47, 0.89)], body mass index [p = 0.01, OR = 0.76, 95% CI (0.15, 1.37)], diabetes [p = 0.01, OR = 1.85, 95% CI (1.14, 3.01)], malignancy [p = 0.001, OR = 2.54, 95% CI (1.46, 4.41)], uncemented prosthesis[p = 0.0003, OR = 0.22, 95% CI (0.10, 0.50)], and longer operation time [p<0.00001, OR = 33.50, 95% CI (23.59, 43.41)] were predictors for DVT following THA. Conclusions Many factors were found to be associated with DVT after THA. We provided references when we met the above characteristics of patients.